2017
DOI: 10.1080/09593330.2017.1345986
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of bioadditives of fuels from biodiesel-derived glycerol by esterification with acetic acid on solid catalysts

Abstract: In this paper, glycerol esterification with acetic acid (AA) was studied on several solid acid catalysts: AlO, Al-MCM-41, HPA/SiO, HBEA, Amberlyst 15 and Amberlyst 36 with the aim of determining the reaction conditions and the nature of the surface acid sites required to produce selectively triacetylglycerol (triacetin). The acidity of the catalysts (nature, density and strength of acid sites) was characterized by temperature-programmed desorption of NH and FTIR of adsorbed pyridine. AlO (Lewis acidity) did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…Meireles et al, [14] reported that acetin could be synthesized successfully at 90°C for 9 hours. The obtained acetin in this study could be possibly increased by increasing the reaction time, and the system should be oxygen-free [22]. So, the higher system's temperature can be reached.…”
Section: Advances In Engineering Research Volume 203mentioning
confidence: 84%
“…Meireles et al, [14] reported that acetin could be synthesized successfully at 90°C for 9 hours. The obtained acetin in this study could be possibly increased by increasing the reaction time, and the system should be oxygen-free [22]. So, the higher system's temperature can be reached.…”
Section: Advances In Engineering Research Volume 203mentioning
confidence: 84%
“…There is thus an increasing surplus of glycerol, creating a need to develop alternative ways to use residual glycerol. 2 Due to its high functionalization, glycerol can be transformed into several value-added products ( Table 1), such as lactic acid, [3][4][5] glyceric acid, 6-8 glycolic acid, [9][10][11] oxalic acid, 9,12 dihydroxyacetone, [13][14][15] glyceraldehyde, [16][17][18] 1,2-propanediol, [19][20][21] 1,3-propanediol, 22-24 1-propanol, 25,26 acrylic acid, [27][28][29] acrolein, [30][31][32] syngas, [33][34][35] mono-, di-, tri-glycerides, [36][37][38] triacetin, [39][40][41] glycerol oligomers, 42,43 and polymers. 44 Lactic acid is conventionally used as an acidulant and preservative in the food industry, in the chemical industry 45,46 as raw material for the production of pharmaceuticals, 47 cosmetics, 48 textiles, 49 leather,…”
Section: Reactionmentioning
confidence: 99%
“…Due to its high functionalization, glycerol can be transformed into several value‐added products (Table ), such as lactic acid, glyceric acid, glycolic acid, oxalic acid, dihydroxyacetone, glyceraldehyde, 1,2‐propanediol, 1,3‐propanediol, 1‐propanol, acrylic acid, acrolein, syngas, mono‐, di‐, tri‐glycerides, triacetin, glycerol oligomers, and polymers . Lactic acid is conventionally used as an acidulant and preservative in the food industry, in the chemical industry as raw material for the production of pharmaceuticals, cosmetics, textiles, leather, and, in a fast‐growing niche market, as monomer for the biodegradable polymer poly‐(lactic acid) or PLA .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to homogeneous systems, heterogeneous catalytic systems facilitate product separation and reusability, among many other benefits. Inorganic solid acids such as niobic acid, silica‐ and zeolite‐supported Lewis acids, zirconium sulfate, and superacids have been extensively studied for esterification reactions 14–20.…”
Section: Introductionmentioning
confidence: 99%